To Determine the Role of Human Papillomavirus in Oral Cancer—A Prospective Study - Mohd Zeeshan; Asim M. Khan; Md Sibgatullah; Jayesh; Rama Brahmam Lanke; Boyapati Ramanarayana; Vikas Singh (Journal of Pharmacy and Bioallied Sciences)
Introduction: Human papillomavirus (HPV) has been implicated in several studies pertaining to oral squamous cell carcinoma (OSCC) in the last several decades. Infection with human papillomavirus (HPV), particularly HPV16 and 18, is the leading cause of squamous cell carcinoma of the neck (SCCHN). Methodology: We selected an adequate number of subjects with the same parameters for both the case and the controls based on detailed case histories, specifically taking into account the adverse habits (tobacco in any form and alcohol) that each subject had recorded. The subjects were selected from the Outdoor Patient Department of Kothiwal Dental College and Research Centre. Before commencing the experimental procedure, all the subjects had undergone blood examinations (HB%, CT, BT, RBS, HBsAg, HIV). Group 1 consisted of 40 subjects, whereas Group 2 had 20 subjects. Result: Human papillomaviruses (HPVs) play an important role in oral cancer, and this research demonstrated a substantial link between HPV-16 and HPV-18 and the disease. Although this research does not allow us to draw any conclusions about cause and effect, our results are consistent with and even expand upon those of previous case–control studies. The presence of HPV causes molecular damage in cells, thereby resulting in cell proliferation and malignant conversions. Therefore, we can conclude that the human papillomavirus significantly contributes to carcinogenesis. Conclusion: Although the current results are based on a limited sample, they provide strong evidence that a larger study of individuals with head and neck cancer is necessary to make firm conclusions.